107k views
5 votes
30 points plz help, I really need it

30 points plz help, I really need it-example-1
User Alphager
by
4.9k points

2 Answers

0 votes

Answer:

A.
-7√(3)\pi

Explanation:

To find the simplified form of that expression, we have to combine like terms. To do this, we should remember that:

ab + cb = (a + c)b


\pi√(3)-8\pi√(3)=(\pi-8\pi)√(3)=((1-8)\pi)√(3)=-7\pi√(3)=-7√(3)\pi

So the simplified form would be
-7√(3)\pi.

I hope you find my answer and explanation to be helpful. Happy studying.

User Eepty
by
5.4k points
6 votes


-7√(3)\pi

Add similar elements

:)Hope you enjoy this:)

User Hein Htet Aung
by
6.1k points